“Moving Forward with Life”: Acceptability of a Brief Alcohol Reduction Intervention for People Receiving Antiretroviral Therapy in South Africa - Myers-Franchi, Bronwyn; Parry, C.D.H.; Morojele, N.K.; Nkosi, S.; Shuper, P.A.; Kekwaletswe, C.T.; Sorsdahl, K.R. (MDPI, 2020)
Background: In South Africa, interventions are needed to address the impact of hazardous drinking on antiretroviral therapy among people living with HIV (PLWH). Participant feedback about these interventions can identify ways to enhance their acceptability. We interviewed participants in a randomized controlled trial of a brief motivational interviewing and problem-solving therapy (MI-PST) intervention about their perceptions of this alcohol-reduction intervention.